A Path‐Based Method for Simulating Large Deviations and Rare Events in Nonlinear Lightwave Systems. Issue 2 (19th April 2016) - Li, J.; Kath, W. L.
Abstract : Errors in nonlinear lightwave systems are often associated with rare, noise‐induced, large deviations of the signal. We present a method to determine the most probable manner in which such rare events occur by solving a sequence of constrained optimization problems. These results then guide importance‐sampled Monte Carlo simulations to determine the events' probabilities. The method applies to a general class of intensity‐based optical detectors and to arbitrarily shaped and multiple pulses.